Convergences and Divergences: Saussure and Chomsky (Palimpsesto, 2019)
The essay aims at a reflection on fundamental issues in linguistics contrasting the positions of Saussure and Chomsky. In general, both authors coincide in conceiving the mental nature of the language, although Saussure configures the object of linguistics from an external perspective. For Chomsky, the concepts are innate in the sense of the semantic features that enter compositionally into the meanings of the words. He also considers phonemes to be innate, understood as a set of distinctive features of a mental nature that, consequently, would be of a universal nature. Finally, in relation to the object of study of linguistics, Saussure’s and Chomsky's visions of the linguistic faculty are contrasted, emphasizing the latter's proposals regarding the creative aspect of language and the poverty of the stimulus in the acquisition of language. It is concluded that the convergences and divergences evidenced between these approaches must be placed in the context of their time to give intellectual justice to both.
Keywords: Linguistic structuralism; generativism; innatism; object of study of linguistics